A world unglued: simultanagnosia as a spatial restriction of attention - Dalrymple, Kirsten A.; Barton, Jason; Kingstone, Alan (Frontiers in Human Neuroscience, 2013)
Simultanagnosia is a disorder of visual attention that leaves a patient’s world unglued: scenes and objects are perceived in a piecemeal manner. It is generally agreed that simultanagnosia is related to an impairment of attention, but it is unclear whether this impairment is object- or space-based in nature. We first consider the findings that support a concept of simultanagnosia as deficit of object-based attention. We then examine the evidence suggesting that simultanagnosia results from damage to a space-based attentional system, and in particular a model of simultanagnosia as a narrowed spatial window of attention. We ask whether seemingly object-based deficits can be explained by space-based mechanisms, and consider the evidence that object processing influences spatial deficits in this condition. Finally, we discuss limitations of a space-based attentional explanation.